Answer:
Step-by-step explanation:
<u>Given vertices of triangle:</u>
- A(1, 2), B(3, 4), C(5, 0)
<u>The centroid is found as the average of x- and y- coordinates of three vertices:</u>
- C = ((x₁ + x₂ + x₃)/3, (y₁ + y₂ + y₃)/3)
<u>Substitute the coordinates into formula:</u>
- C = ((1 + 3 + 5)/3, (2 + 4 + 0)/3) = (3, 2)
Correct choice is B
Answer:
11
Step-by-step explanation:
Replace the variable xx with −1-1 in the expression.
f(−1)=−3⋅−1+8f(-1)=-3⋅-1+8
Simplify the result.
Tap for fewer steps...
Multiply −3-3 by −1-1.
f(−1)=3+8f(-1)=3+8
Add 33 and 88.
f(−1)=11f(-1)=11
The final answer is 1111.
=11
I want brainless pleased
Answer:
x = 36
Step-by-step explanation:
(3/4)*x-((2/3)*x)-4 = (1/6)*x-7 // - (1/6)*x-7
(3/4)*x-((2/3)*x)-((1/6)*x)-4+7 = 0
(3/4)*x+(-2/3)*x+(-1/6)*x-4+7 = 0
3-1/12*x = 0 // - 3
-1/12*x = -3 // : -1/12
x = -3/(-1/12)
x = 36
Answer: The chosen topic is not meant for use with this type of problem. Try the examples below.
Step-by-step explanation:
(-3, 1.5)....simply add the x coordinates together, divide them by two, and then do the same for the y coordinates.